Comparative effectiveness of neoadjuvant chemotherapy plus surgery versus concurrent chemoradiotherapy in stages IB2 to IIB of cervical cancer: a meta-analysis - Gao, Yue; Wang, Huali; Jiang, Meng (Frontiers in Oncology, 2024)
Objectives: To assess the comparative efficacy of neoadjuvant chemotherapy followed by surgery (NACT+S) versus concurrent chemoradiotherapy (CCRT) for patients with cervical cancer stages IB2 to IIB.Method: An exhaustive literature search was conducted up to November 2023 in databases including PubMed, Embase, Web of Science, and the Cochrane Library, focusing on disease-free survival (DFS) and overall survival (OS). Data were analyzed using STATA version 15.The meta-analysis included data from two randomized controlled trials and eight retrospective cohort studies, totaling 2,879 patients with stages IB2 to IIB cervical cancer. Pooled data showed no significant difference in OS (hazard ratio [HR] 0.71, 95% confidence interval [CI]: 0.51 to 1.00, p = 0.052) and DFS (HR 0.65, 95% CI: 0.38 to 1.14, p = 0.132) between NACT+S and CCRT. Subgroup analysis revealed that NACT+S provided a better OS in Asian populations, retrospective cohort studies, TP regimen chemotherapy, and multivariate analysis.The findings indicate that CCRT and NACT+S are comparably effective for treating cervical cancer stages IB2 to IIB. Notably, in specific subgroups such as Asian patients and those receiving the TP regimen, NACT+S appears to enhance OS.